2016
DOI: 10.1016/j.jbo.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

The role of hematopoietic stem cell niche in prostate cancer bone metastasis

Abstract: Approximately 80% of prostate cancers exhibit some degree of bone metastasis. The role of the bone marrow and the hematopoietic stem cell (HSC) niche in attracting metastatic cells and maintaining dormancy of disseminated tumor cells (DTCs) is an increasingly important topic towards the development of novel prostate cancer therapies. This paper reviews aspects of the HSC niche that lead to prostate cancer cell homing and dormancy in the bone marrow. This review also discusses the role of DTCs in the niche envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 36 publications
(43 reference statements)
1
13
0
Order By: Relevance
“…Metastatic, and particularly castrate-resistant prostate cancer (CRPC), remain challenging to treat [ 23 ]. It is thought that the bone marrow microenvironment plays a pivotal role in promoting bone metastasis, possibly facilitating the transition to CRPC forms, and impacting on PCa cell drug response [ 24 27 ]. A barrier to understanding these interactions, in both drug development and testing, is the lack of in vitro models that adequately mimic aspects of the bone marrow microenvironment in a practical and high throughput manner.…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic, and particularly castrate-resistant prostate cancer (CRPC), remain challenging to treat [ 23 ]. It is thought that the bone marrow microenvironment plays a pivotal role in promoting bone metastasis, possibly facilitating the transition to CRPC forms, and impacting on PCa cell drug response [ 24 27 ]. A barrier to understanding these interactions, in both drug development and testing, is the lack of in vitro models that adequately mimic aspects of the bone marrow microenvironment in a practical and high throughput manner.…”
Section: Discussionmentioning
confidence: 99%
“…Most cancer-related deaths are caused by metastatic spread rather than the primary tumour. Breast, prostate, renal, lung and thyroid cancers preferentially metastasise to the bone ( Virk and Lieberman, 2007 ), and it is postulated that disseminated cancer cells follow the cytokine signalling pathways that are usually used by the HSCs to home to the bone marrow microenvironment ( Decker et al, 2016 ; Reagan and Rosen, 2016 ). Once there, the disseminated cancer cells lie dormant or interact with the resident bone cells to stimulate growth factor release and other pro-tumorigenic signals ( Ottewell, 2016 ).…”
Section: Humanised Bone Approaches For Disease Modellingmentioning
confidence: 99%
“…It is worth noting that normal bone houses the hematopoietic stem cell (HSC) niche, comprised by hematopoietic and mesenchymal cell populations, which provide homing signals to HSCs and regulate HSC selfrenewal (Taichman et al 2010). It has been suggested that DTCs can precondition the metastatic niche and compete with and occupy the HSC niche to facilitate metastasis (Decker et al 2016).…”
Section: Cancer Progression To Established Bone Metastasesmentioning
confidence: 99%
“…The mechanism that makes cancer cells leave the dormant state and start growing is ill-defined and a subject of intense study. It has been proposed that there are signals and factors from the metastatic/HSC niche, including FGF2, that can play a role in exiting dormancy (Decker et al 2016).…”
Section: Cancer Progression To Established Bone Metastasesmentioning
confidence: 99%